Resources and strategies for teaching statistics and data analytics in higher education (2022)
The purpose of this study is to present a literature review analysis on the teaching of statistics and data analytics in higher education. The assessment includes examining the role played by specific factors as mediators of teaching-learning processes. These factors include: disciplinary and pedagogical training of teachers, teaching styles, classroom experiences, use of didactic resources, and context. The literature review revealed that there is a need to create and develop innovative learning environments that transform the teaching of statistics at the university level, starting from rethinking the contents and curricula to favor the social dimension and the humanistic and complex thinking of students. It is concluded that, currently, the generalization of digital media and social networks imposes new challenges for teaching statistics and data analytics in the context of data science, machine learning, and big data.